La nutrición y su relación con el desarrollo cognitivo en los niños de preparatoria de la unidad educativa Manuel Agustín Cabrera Lozano de la ciudad de Loja. Periodo lectivo 2017-2018 - Cabrera Cardenas, Yajaira Jackeline (2018)
The present work investigative called, THE NUTRITION AND IST RELATION WITH THE COGNITIVE DEVELOPMENT IN THE CHILDREN OF PREPARATORY OF UNIDAD EDUCATIVA MANUEL AGUSTÍN CABRERA LOZANO OF LOJA CITY. PERIOD 2017-2018; it was developed on the basis of the established in the Academic Regime Regulation of the National University of Loja. The general aim raised in the project of thesis was to identify since the nutrition influences the cognitive development the children of preparatory of the UNIDAD EDUCATIVA MANUEL AGUSTÍN CABRERA LOZANO OF LOJA CITY, period 2017-2018, with the purpose of suggesting improvements to this problematics. This work investigative is of descriptive character, it was realized applying the following methodology, the methods that were used: the scientific method, analytical - synthetic method and descriptive method, the techniques and instruments used were: the survey that was applied to the family parents to determine the incident of the Nutrition in the Cognitive Development of the girls and children, the interview was applied to the teacher to obtain information it brings over of the raised problem and the test of cognitive skills applied to the children and girls, to evaluate the Cognitive Development. In agreement to the results of the test of cognitive skills applied to the children from five to six years of age of preparatory of the Unidad Educativa Manuel Cabrera Lozano it is concluded that 74,1% of the students investigated if they carry out with the applied activities of cognitive character that was evaluated, while 25,9% of children did not carry out with these activities. According to the results of the survey for parents, it is concluded that 61% of the surveyed consider that nutrition affects the cognitive development of their children, while the remaining 39% consider that they do not.